The concept of security in the Holy Quran: Its derivatives, and its importance in life (Journal of Human Sciences, 2024)
This research deals with an analytical study in the field of interpretation of the Holy Qur’an, as it includes security verses and their derivatives in the Holy Qur’an. These verses are then contemplated and their meanings are used to explain the importance of security in    People's lives, and learning about the factors that ensured security in society, the most important of which is the Holy Qur’an, which made the concept of security comprehensive and complete in human life. This is done by explaining and presenting the concept of security.    Its derivatives in the Holy Qur’an, citing some of the sayings of scholars in this regard, and explaining its aspects, then presenting the verses related to this matter, and studying the aspects of inference through the sayings of commentators in this matter.   Theme.    The verses, in addition to addressing the purposes of security and its importance in people’s lives.   As a result, this research was given the title: (The concept of security in the Holy Qur’an: its derivatives, and its importance in life).   After this arrangement comes the conclusion, which includes the most important results and recommendations, followed by an index of sources and references.